Peran Influencer dalam Investasi Cryptocurrency: Literasi Keuangan Digital Mediator ataukah Moderator? - Wijaya, Lientang; Kusuma, I Gede Wahyu Artha; Khouroh, Umu (University of Merdeka Malang, 2024)
In the context of significant growth in cryptocurrency in Indonesia, investment influencers on social media often provide information that affects investment behavior. Digital financial literacy becomes crucial in ensuring wise investment decisions, especially in understanding the risks and potential benefits of cryptocurrency. This research explores the role of influencers in cryptocurrency investments in Indonesia, with a focus on digital financial literacy as a mediating factor. Data were collected using a survey method with a sample of 100 respondents. Data analysis employed SEM-PLS. The study results indicate that influencers and digital financial literacy affect cryptocurrency investment decisions. Digital financial literacy acts as a mediator, not a moderator. These findings highlight the importance of comprehensive financial education in addressing this increasingly popular investment trend.